RESEARCH AND DEVELOPMENT OF MENTAL RESILIENCE AS AN ADAPTIVE MECHANISM IN SERVICEMEN - Larysa Chernobai; Oleg Khairulin (Scientific Journal of Polonia University, 2022)
The article is devoted to the analysis of theoretical approaches and psychological aspects of the study of mental resilience, as one of the factors that helps maintain and restore mental health of the individual and to explore mental resilience as an adaptive mechanism to respond to adverse factors of combat conditions for servicemen. In modern scientific research, resilience distinguishes two main approaches to its understanding: 1) resilience as an individual characteristic (ego-resiliency), a personality trait that protects against the ills of life and is manifested through such qualities as flexibility, agility, ingenuity and strength of character, and also the ability to adapt to functioning in different external conditions; 2) resilience as a dynamic process in which positive adaptation occurs in conditions of trouble. In this sense, resilience is conceptualized as a continuous, active process of emergence or development of new forces and resources of adaptation and recovery, which has uneven dynamics in the face of new risks. The question of whether resilience is a trait or a process is still debated, but there is a common understanding that this concept describes the activities of individuals, families and groups to function, adapt and cope successfully despite psychological, social, cultural and / or physical difficulties. Resilience (as a trait and process) is manifested in people during the continuation of their development.